The Role of ESG Disclosure in Moderating Financial Distress on Company Value - Faradilla Saulina Febriani; Zaky Machmuddah (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2026)
Market value volatility in manufacturing threatens corporate sustainability. This research examines how ESG disclosure moderates the link between financial distress and firm value. The sample comprises 85 Indonesian companies selected through purposive sampling. Data came from annual reports, IDX financial statements, and Bloomberg ESG ratings. We analyzed data using regression analysis in IBM SPSS Statistics 25. Results show financial distress significantly lowers firm value; greater financial pressure reduces valuation. ESG disclosure, as a moderator, eases this negative effect, lessening the impact of financial distress. These findings support Signaling and Legitimacy Theory: financial distress sends negative signals, while ESG disclosure preserves legitimacy and sends positive signals to investors. ESG disclosure’s moderating role is key in shaping how markets perceive the effects of financial distress on firm value. This study contributes to financial risk management and corporate sustainability during economic challenges and urges companies to adopt risk-mitigation and sustainable practices.